Migration processes as an important context of old age in modern society - Majewska-Kafarowska, Agnieszka (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
In this text, the author devotes attention to the issue of migration, touching upon themes that are related to aging, aging, quality of old man’s life. The reflections on the specificity of migration processes characterize the gerontological point of view of the problem. The author shows the specifics of migration, paying attention to their entanglement with the postmodern processes of globalization, thus delineating the context of the migration phenomenon, which becomes commonplace and affects both the younger and older, albeit the latter in a particular way.